Evaluating the performance of modern rural management (Dehyari) in improving social contexts and attracting financial resources for the development of rural entrepreneurship in Khalilabad - Akherati Ivari, Ayoub (2021)
Entrepreneurship is one of the most important tools for planning and achieving the development of rural communities. Today, due to the problems in these communities, attention and emphasis on rural entrepreneurship is very important; Because entrepreneurship can play an effective role in improving the economic and living conditions of villages by creating new employment and income opportunities, and the present study aims to evaluate the performance of modern rural management (rural) in improving social contexts and attracting financial resources. It has been prepared for the development of rural entrepreneurship in Khalilabad city. The present research is applied in terms of purpose and in terms of descriptive-analytical method, which used library and field methods to collect information and a researcher-made questionnaire for field data. The sample population was randomly studied using Cochran's formula including 370 people in 23 villages of the city. The results obtained in the villages of the city show that the performance of rural villagers in Khalilabad city in order to develop rural entrepreneurship has been weak. Villages have not improved the social context and attracted financial resources for the development of rural entrepreneurship and have not been able to achieve the desired goals.